2014
DOI: 10.1007/s13238-014-0097-1
|View full text |Cite
|
Sign up to set email alerts
|

Tackling the tumor microenvironment: what challenge does it pose to anticancer therapies?

Abstract: Cancer is a highly aggressive and devastating disease, and impediments to a cure arise not just from cancer itself. Targeted therapies are difficult to achieve since the majority of cancers are more intricate than ever imagined. Mainstream methodologies including chemotherapy and radiotherapy as routine clinical regimens frequently fail, eventually leading to pathologies that are refractory and incurable. One major cause is the gradual to rapid repopulation of surviving cancer cells during intervals of multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Intriguingly, NF‐κB was identified as a key signaling node that actively mediates WNT16B production. Cell culture experiments and tumor xenograft models proved the protective effect of fibroblast‐derived WNT16B, indicating that WNT16B secreted by stroma attenuates cancer cell apoptosis induced by genotoxicity, and compromises drug response through activation of a DNA damage secretory program (DDSP) (Fig. ).…”
Section: Impact Of Damaged Tme To Clinical Therapiesmentioning
confidence: 99%
“…Intriguingly, NF‐κB was identified as a key signaling node that actively mediates WNT16B production. Cell culture experiments and tumor xenograft models proved the protective effect of fibroblast‐derived WNT16B, indicating that WNT16B secreted by stroma attenuates cancer cell apoptosis induced by genotoxicity, and compromises drug response through activation of a DNA damage secretory program (DDSP) (Fig. ).…”
Section: Impact Of Damaged Tme To Clinical Therapiesmentioning
confidence: 99%
“…The transcription factor nuclear factor-jB (NFjB) is a major regulator of pro-inflammatory genes including cytokines and chemokines (IL-6, RANTES and IL-8) [26]. In the process of carcinogenesis, mal-developed cells activate NF-jB pathway from intrinsic imbalance or extrinsic signals in the tumor microenvironment [27,28]. In this article, we found that miR-526a expression led to decreased cell apoptosis by TNF-a-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The study presents new opportunities for future advanced treatments that rationally integrate agents to confine the TME activities. For instance, depleting stroma-derived WNT16B, which would specifically overcome such a "new" but not "minor" TME-associated resistance mechanism [57,60]. As supporting evidence, CAFs are similarly enriched in colorectal cancer (CRC) during the post-therapy stage and display enhanced cytokine IL-17A, which helps maintain the tumor infiltrating cells (TICs) through activation of NF-κB signaling [61].…”
Section: The Therapeutically Remodeled Tme Alters Clinical Outcomementioning
confidence: 99%
“…Upon genotoxic insults, NF-κB acts as a key signaling node that actively mediates WNT16B production. Cell-based experiments and tumor transplant models demonstrated the protective effect of fibroblast-derived WNT16B, indicating that WNT16B secreted by stroma attenuates cancer cell apoptosis induced by genotoxicity, and counteracts drug response through activation of a DNA damage secretory program (DDSP) [56][57][58][59] (Figure 2). The study presents new opportunities for future advanced treatments that rationally integrate agents to confine the TME activities.…”
Section: The Therapeutically Remodeled Tme Alters Clinical Outcomementioning
confidence: 99%
See 1 more Smart Citation